Minimum eligibility age for social pensions and household poverty: Evidence from Mexico. - Ávila‐Parra, Clemente; Escamilla‐Guerrero, David; Gálvez‐Soriano, Oscar (Economic Inquiry, 2024)
This paper examines the impact of social pensions on old‐age poverty. To achieve causal identification, we leverage the reduction in the minimum eligibility age of Mexico's flagship non‐means‐tested social pension program. We find that the program's expansion significantly reduced extreme poverty, mainly among indigenous seniors and in rural areas. However, it had negligible effects on labor force participation, suggesting that social pensions were not effective in ensuring minimum economic well‐being and simultaneously inducing retirement among seniors at early stages of old age. The program's small cash transfer and mistargeting are among the main explanations.